Influence of ethanol on the longevity and delayed senescence of bougainvillea flower - Hossain, A.B.M.S.; Boyce, A.N. (2008)
The study was carried out to investigate the effect of ethanol (ET) at different concentrations on longevity and senescence delay in bougainvillea flowers. The treatments were water (control), 2, 4, 8, 10, 20, 30, 40, 50 and 70 ET. Positive response was found in case of 4, 8 and 10 of ET after a certain period of treatment application. Dry weight was higher in lower concentrations of ethanol and lower in higher concentrations. Flower longevity was 2 days longer in 4, 8 and 10 ET than in water control and other concentrations of ethanol. Petal wilting and abscission occurred 2 days later in 4, 8 and 10 ET than in control. Perianth abscission also appeared 2 days later in 4, 8 and 10 ET than in control. However, petal discoloration (color change) was later in control, 2, 4, 8 and 10 than in 20, 30, 40, 50 and 70 ET. The results showed that flower vase life was significantly affected by ethanol concentrations as well as longevity was longer in 4, 8 and 10 ET than in water control and other concentrations.